Modelling of the bio-ecological drainage system using infoworks SD / Hamed Benisi Ghadim - Hamed, Benisi Ghadim (2016)
Nowadays, Malaysia has been widely practiced rapid disposal, localized, reactive and mono-functional drainage concepts. With increasing in urbanization and population in urban areas the essentiality to new approach in drainage system is necessary. One of these approaches that launched in Malaysia is Bio-Ecological Drainage System (BIOECODS). The Bio-Ecological Drainage System (BIOECODS) is a Sustainable Urban Drainage System (SUDS) that was developed by the River Engineering and Urban Drainage Research Centre (REDAC) and Drainage and Irrigation Department (DID) to demonstrate the utilization of ‘control at source’ approaches for urban stormwater management. It is an environmentally friendly drainage system that was designed to increase infiltration, reduce peak flow at outlets, improve water quality, and increase the aesthetic value of the surrounding area through a number of SUDS components. Major components of BIOECODS systems are ecological grasses swale, and ecological ponds namely retention pond, dry detention pond and wet land. The BIOECODS combines three engineering techniques to manage stormwater based on control at source approach, namely infiltration, storage and conveyance system by swales, subsurface drainage modules, dry ponds and constructed wetland. The main objectives of this study are to develop a model with integrated surface and subsurface conveyance with high accuracy compare to real situations, increase understanding about rainfall-runoff respond in BIOECODS system and assessment of Best Management Practices (BMP) components in urban stormwater management, in peak discharge attenuation and surface and sub-surface flow relationship. A new technique has been adopted in the effort to fully integrate or couple both the surface and on-line subsurface conveyance (single node) to present overall interaction of this component in the BIOECODS system. The new technique has been used Storm Water Management Model (SWMM) model which uses the non-linear reservoir method and Kinematic wave approximations of the Saint-Venant equation to describe overland flow routing and Horton method in conjunction to Soil Conservation Service Method (SCS) used to model infiltration or subsurface flow. The observed data in terms of water level, and velocity in the constructed monitoring stations in the study area for different rainfall events is compared with that obtained from the model’s simulation. The calibrated and validated model for the whole watershed area was then used to consider different scenarios to evaluate the effectiveness of BIOECODS and each BMP component in decreasing water level and respectively peak flow attenuation. Overall, the results indicate a peak water level reduction for the total study area of 28000m2 of more than 100% during low intensity events, and in the range of ±60-85% for events of medium and high intensity. They also show that the lag time to peak for events of medium and high intensity were ±15 minutes. The results also show that ecological swale with on-line subsurface drainage system is very effective in terms of decreasing peak flow and improving the infiltration characteristic of an urban area. Also subsurface drainage module integrated with swale is able to cater a percentage of surface runoff volume approximately 60% to 76% for rainfall events. Through this study, the technique being utilized to define the surface and on-line subsurface conveyance system is proved to be successful to integrate the flow in both components and their interactions. Although the results doesn't only represent the findings for BIOECODS system, the modelling efforts for such a sustainable drainage system could be used for the entire world and all SUDS components. The effort of this modelling can illustrate new the idea to the designing, planning and strategies for preventing flash flood in urban areas and also to ensure that SUDS systems will work properly during the rainfall events.